IMPLEMENTASI VPN SERVER MENGGUNAKAN PROTOKOL L2TP DAN IPSEC PADA PT. MULTI TERMINAL INDONESIA - FIkri, Hermawan (Universitas Respati Indonesia, 2024)
This research was conducted with the aim of assisting in the activation and security of hardware and software devices using a VPN L2TP/IPSec server and client network. namely configuring a Mikrotik router network based on VPN L2TP/IPSec server and client, by connecting two public networks into one local network. and the hardware or software devices in question are the SAP financial system, Avaya telephone devices, and CCTV monitoring. By creating a VPN L2TP server and client path, it can help and facilitate employees in working, both in branch areas and in areas outside the PT office. Multi Terminal Indonesia. The analysis method used in this research is the grounded method, where the grounded method itself is carried out by holding data in the field, both in formulating problems, building hypotheses, and drawing research conclusions. Therefore, this research is very dependent on the experience and credibility of the researcher. Keywords: Network, VPN, L2TP, IPSec